Análise de fitólitos aplicada a reconstrução paleoambiental (vegetação e clima) na superfície incompletamente aplainada VI – Campo Erê (SC) no pleistoceno tardio - Cecchet, Fernanda Aparecida (2015)
Phytoliths are microscopic particles of silica, or biomineralizations, formed during the growth of the plant, through the absorption of dissolved monosilicic acid (H4SiO4) solute from the soil. Phytoliths remain preserved in soil under certain environmental conditions making them a great ally in paleoenvironmental reconstruction studies. In South-West Paraná and North-West Santa Catarina, where there were large areas of Araucaria moist forests (AMF), the Genesis and Evolution of Geomorphological Surfaces and Surface Formations research group (GPGESGFS) has carried out dedicated research using diverse biological proxies, including phytoliths, in order to understand the principal factors and processes which were active in the formation of the current relief and in the evolution of the landscape of this region. Considering the hypothesis of environmental changes (climate and vegetation) in the South of Brazil during the Pleistocene/Holocene, the present study has as its main objective understanding the environmental dynamic during the Late Pleistocene and Holocene, which may have acted on the evolution of the landscape of Campo Erê (SC), incomplete planation surface VI. The results obtained through routine physical and chemical analyses of the phytolith assemblage, the ratios of the stable carbon isotopes and 14C dating of the humin fraction, have enabled us to conclude that the soil studied in Campo Erê (SC), a typical distroferric red nitosol with humic A horizon, developed in situ through pedogenic evolution from the material of origin, basalt. Since the middle of the last glacial maximum (18.060-17.845 Years Cal. BP.) this profile developed beneath vegetation, possibly less leafy than the current vegetation, with a mixture of C3 (grasses, trees and bushes) and C4 (grasses) plants. This pattern of vegetation remained until the beginning of the Holocene (8.055-7.960 Years Cal. BP.) From the Middle Holocene on, there occurred an opening up of the vegetation, marked by greater participation of C4 grasses, possibly a campo sujo (a herbaceous layer with occasional small trees), shown as much by the isotopic signal as by the phytolith assemblage. This vegetation lasted until approximately 1.875-1.715 years Cal BP, once again becoming vegetation formed predominantly by C3 plant species of photosynthetic cycle, until the formation of the current AMF found in the study area. At no time were signs of dense tree formation detected, but instead leafy vegetation, which was at times more open and at others more closed. This characteristic is prominent in the vegetation of the south of Brazil, where extensive areas of AMF are surrounded by grasslands forming great mosaics on the landscape. All the climatic oscillations, however small, reflect the retreat or advance of this forest over grassland or vice-versa